Integrating Biotechnology and Molecular Biology: Advancements and Future Prospects - Ahmed Falih Salman Idan; Noor Maan Mohammed; Asmaa Hamid Khleef Mahwish; Hala Aziz Ibrahim Badawi; Hawraa Dafer Kareem Abbas (American Journal of Biology and Natural Sciences, 2025)
The quality and nutrition of the food products decide the health status of the global population physically and mentally, not the quantity . After the predictions regarding problems in availability with food and nutritional securities in the coming years, it was expected that these securities could only be possible by achieving rapid and higher genetic gains in food crops having the dual wellness of enhanced quality and nutrition as well as adaptation to adverse agro-climatic conditions. Although ongoing efforts of classical breeding have been partially successful in increasing per production productivity, still new approaches need to be evaluated to accelerate the progress. Available biotechnological interventions could be useful and faster approaches, if integrated with ongoing efforts of conventional breeding. With the success of micropropagation and tissue culture-based interventions in crop species, new dimensions were added by considering biotechnological genomics in agriculture. The last 3 decades’ rapid advances in different biotechnological processes, approaches, and technologies have revolutionized the ongoing efforts of agricultural research for an increased tolerance of abiotic and biotic factors on one hand, and the development of the genomic resources of different model and crop plant species on the other hand, expanding better understanding about the evolutionary process of plants at the genome level. The advances in these technologies were the basis for developing various better editing tools. Besides developing resistance against different abiotic and biotic factors these biotechnological were also useful to enhance the essential quality and nutritional status of food products, as well as understanding resistance genomics. Although partial success was realized through transgenic plants in few cereals and pulses crop species, there was an imprecision and unpredictable adverse effect on biological, biochemical and biophysical factors in some varieties. Specific sequences and tissue-specific problems of these transgenes in developed transgenic plants were the major constraint. Since the last 2 decades, these have been the basis for developing RNAi-mediated host-induced vectors with greater efficiency, specificity and predictability, understanding the mechanisms of resistance, and the molecular strategies of viruliferous pathogens. These approaches could be convenient and more alluring for developing non-toxic, alluring, and environmental benign plants having less off types. Furthermore, the current advanced technology support helps to understand everything beyond the genome, among species, among species and genotype and so on with different important traits. Enormous specificity and sensitivity of technology development have also accelerated the discovery and identification of new alleles or proteins related to biotic factors.